The Influence Of Career Development, Work Environment And Workload On Job Satisfaction And Its Impact On Employee Performance - Akmal, Muhamad; Masriah, Imas; Supratikta, Hadi (International Journal of Management and Digital Business, 2024)
Objectives – Company performance is highly dependent on public administration personnel, including individual resources to work in all organizations. Management performance can be improved by ensuring that each level of the organization has adequate business requirements and clear plans to support management objectives. This research uses a quantitative approach with a type of causal research. This research focuses on PT. SSP contact center employees. as a population of 100 individuals. The saturated sampling method was used to select the research sample, which means the entire population was included. The questionnaire uses a Likert scale which is one of the questionnaire measuring tools. SmartPLS version 3. is software used to analyze data related to various variables. Innovation/Value - Learning organizations and employee empowerment drive continuous improvement, innovation and adaptability, enabling employees to make informed decisions and contribute to organizational goals. This helps organizations align and maintain competitive advantage by improving careers, environments and jobs.